Parents’ Experience with Remote Learning during COVID-19 Lockdown in Zimbabwe - Lockias Chitanana (Journal of Open, Flexible and Distance Learning, 2023)
The closure of primary schools during the COVID-19 pandemic led to a rapid shift to remote learning, placing more responsibility for learning on parents and guardians. This study sought to explore parents’ experience while engaging in their children’s remote learning during that period. The study is particularly timely in light of a dramatic growth in remote learning due to the continued disruption of face-to-face learning in schools. A study of parents’ experience may yield useful data and identify trends to inform the development of programmes and policies targeting parental needs and support in this emerging form of learning. A descriptive qualitative design was used to conduct this study so that relevant responses could be sought to get insights into parents’ experience during the COVID-19 pandemic. Questionnaires and online interviews were used to collect data from a purposive sample of 25 parents, whose selection was based on their involvement in their children’s home learning and access to internet connectivity in the home. The results revealed that parents found the sudden closure of schools extremely disturbing, and they were concerned about their children’s routines. Parents highlighted that they had difficulties with balancing responsibilities, adjusting to remote learning, children’s lack of motivation to learn, poor accessibility of learning material, lack of capacity to assist multiple children, and finding appropriate space for learning. The results of the study have important implications for policy, and generated strong recommendations for teachers, school authorities, and policymakers.